Choosing the Right IaC Tool for Building Reusable Cloud Infrastructure - Kalliomaa, Niko (My University, 2024)
This study examines the critical role of Infrastructure as a Code (IaC) tools in automating the provisioning, configuration, and management of cloud infrastructure, which is essential for the rapid growth and success of organizations in the cloud computing domain. By enabling cloud developers to define infrastructure in code format, IaC tools facilitate easy versioning, change tracking, and deployment automation. This capability ensures that infrastructure can be consistently and reliably deployed across various environments, significantly reducing the risk of errors and downtime. However, the implementation of IaC tools without adequate knowledge can introduce risks. The research emphasizes the importance of selecting the right IaC tool, considering factors like scalability, security, and compliance enhancement. The study aims to compare the features, ease of use, scalability, security features, and integration capabilities of the most utilized IaC tools, providing insights into building reusable cloud infrastructure. Through a comprehensive exploration of cloud services evolution, prevalent cloud resources, and a detailed analysis of selected IaC tools, this thesis offers a comparative assessment of these tools across different cloud service providers. The findings, derived from empirical tests, offer a deep dive into the technical nuances, qualitative attributes, and integration potential of these tools, paving the way for future research in the field of cloud computing and infrastructure development.
Keywords: cloud computing, infrastructure as code, pulumi, terraform, ansible, devops